Late Antique and Medieval Landscapes of the Nemea Valley, Southern Greece - Cloke, Christian; Athanassopoulos, Effie (Journal of Greek Archaeology, 2020)
In the last 40 years regional survey projects and excavations in the Aegean region have produced a rich record of Late Antique and Medieval land use and settlement. They have provided information about rural sites and villages, subjects that are poorly covered by historical sources. In this paper we examine the contribution of surface survey, along with information derived from excavation, to the understanding of these periods. The case study comes from the region of Nemea, in southern Greece, which has been the focus of excavations by the University of California-Berkeley and an intensive survey as part of the Nemea Valley Archaeological Project (NVAP) (Figure 1a-b).